A tudor domain protein SPINDLIN1 interacts with the mRNA-binding protein SERBP1 and is involved in mouse oocyte meiotic resumption. - Ting Gang Chew (Public Library of Science (PLoS), 2013)
Mammalian oocytes are arrested at prophase I of meiosis, and resume meiosis prior to ovulation. Coordination of meiotic arrest and resumption is partly dependent on the post-transcriptional regulation of maternal transcripts. Here, we report that, SPINDLIN1 (SPIN1), a maternal protein containing Tudor-like domains, interacts with a known mRNA-binding protein SERBP1, and is involved in regulating maternal transcripts to control meiotic resumption. Mouse oocytes deficient for Spin1 undergo normal folliculogenesis, but are defective in resuming meiosis. SPIN1, via its Tudor-like domain, forms a ribonucleoprotein complex with SERBP1, and regulating mRNA stability and/or translation. The mRNA for the cAMP-degrading enzyme, PDE3A, is reduced in Spin1 mutant oocytes, possibly contributing to meiotic arrest. Our study demonstrates that Spin1 regulates maternal transcripts post-transcriptionally and is involved in meiotic resumption.